PRESIDEN PEREMPUAN: STUDI ATAS PANDANGAN KIYAI HUSEIN MUHAAMMAD - Gazali, Gazali; Syafrizal, Syafrizal (UIN Sunan Kalijaga Yogyakarta, 2020)
This article addresses the issue of a female president according to K.H. Husein Muhammad. This figure is used as a reference material, first, because of his high attention to gender issues. Second, women's leadership in Indonesia is a discourse and vehicle that develops dialectically and is very interesting to be used as a reference material, especially since Indonesia is the largest Muslim country in the world where gender issues are still in the